The Use of Saturated MgSO4 Compared to Saturated Sucrose in the Flotation Method to Identify Eggs and Larvae of Soil-Transmitted Helminths from Plantation Soil - Nidya Husna Kholidah; Yunita Armiyanti; Dwita Aryadina Rachmawati; Bagus Hermansyah; Yudha Nurdian (Journal of Agromedicine and Medical Sciences, 2021)
Worms infection is still common in Indonesia with a prevalence that varies around 40% -60% at all ages. This disease can be caused by infection of Soil-Transmitted Helminths (STH) that require soil media to infect humans. The many plantation lands in Jember are a suitable environment for the development of STH and STH identification in soil can be done by flotation method using MgSO4 solution or sucrose. The comparison of the effectiveness of the MgSO4 solution with the sucrose solution has not been widely studied. Therefore, the aim of this study was to compare the efficacy of using saturated MgSO4 solution with saturated sucrose to identify eggs and larvae of STH in Sumber Wadung plantation soil, Hargomulyo Village, Silo District, Jember Regency using the flotation method. Soil samples were taken as many as 35 samples in the garden area, 35 samples around the river, and 35 samples in residential areas,. The results of identification of STH eggs and larvae obtained Ascarid eggs (1.9%) and Hookworm larvae (0.01%). The number of positive soil samples containing STH eggs and larvae using different solutions is the same as three samples (0.02%).The Wilcoxon test results showed that there was no difference in the results of using the MgSO4 solution with the sucrose solution in the flotation method (p> 0.05) so that the MgSO4 solution and sucrose solution could be used to detect eggs and larvae of STH worms and had the same effectiveness. Keyword: Soil-transmitted helminths, saturated MgSO4, saturated sucrose, flotation